Monitoring the mortality impact of COVID-19 in Europe: What can be learned from 2009 influenza H1N1p mortality studies?. (January 2021) - Staadegaard, Lisa; Taylor, Robert J.; Spreeuwenberg, Peter; Caini, Saverio; Simonsen, Lone; Paget, John
Highlights: Monitoring mortality is a key indicator for policy makers during a pandemic. In 2009, laboratory-confirmed flu deaths were a good measure of mortality in the EU. All-cause mortality is probably a better indicator of SARS-CoV-2 mortality. All countries in Europe should join the EuroMOMO mortality surveillance project. EuroMOMO countries should present absolute mortality numbers and mortality rates. Abstract: Objectives: Understanding the proportion of pandemic deaths captured as 'laboratory-confirmed' deaths is crucial. We assessed the ability of laboratory-confirmed deaths to capture mortality in the EU during the 2009 pandemic, and examined the likelihood that these findings are applicable to the SARS-CoV-2 pandemic. Methods: We present unpublished results from the Global Pandemic Mortality (GLaMOR) project, in which country-specific mortality estimates were made for the 2009 influenza H1N1p pandemic. These estimates were compared with laboratory-confirmed deaths during the 2009 pandemic to estimate the ability of surveillance systems to capture pandemic mortality. Results: For the 2009 influenza H1N1p pandemic, we estimated that the proportion of true pandemic deaths captured by laboratory-confirmed deaths was approximately 67%. Several differences between the two pandemics (e.g. age groups affected) make it unlikely that this capture rate will be equally high for SARS-CoV-2. Conclusion: The surveillance of laboratory-confirmed deaths in the EU during the 2009 pandemic was more accurate than previously assumed. We hypothesize that this method is less reliable for SARS-CoV-2. Near-real-time excess all-cause mortality estimates, routinely compiled by EuroMOMO, probably offer a better indicator of pandemic mortality. We urge more countries to join this project and that national-level absolute mortality numbers are presented.